A Comprehensive Assessment of Drought and Climate Change - Qian yimin; Yao Shuiping; Yan Kun; Tang Wenjia (MATEC Web of Conferences, 2018)
Drought is one of slow onset natural hazards with great impacts in many aspects, such as economy, agricultural and human health. To well manage drought, the areal coverage, duration and frequency can be analyzed and estimated to provide insight into historical perspective of drought events as well the long-term variation of climate in the study area. This study tries to explore the natural of drought including its definitions, categories, trigger mechanism and possible mitigation methods. This research studies the drought characteristics in Wyoming, United States based on the rainfall data from the U. S Historical Climatology Network (USHCN). The main approach is Standardized Precipitation Index (SPI), which provides the means to analyze drought at different time scales and discusses the relationship between drought and climate change.